2
$\begingroup$

Using the quotient rule and the chain rule you get $$ \frac{d}{dy}\left(\frac{dx}{dy}\right)=\frac{d}{dy}\left(\frac{1}{\frac{dy}{dx}}\right) =\frac{d}{dx}\left(\frac{1}{\frac{dy}{dx}}\right)\times \frac{dx}{dy}\\$$

I don't understand how this came. First is dy/dx always gonna be equal to dx/dy? Wouldn't the function have to be inverse to each other. And how to do chain rule in cases like this... I didn't get how the differentiation is done here. Can you explain with a simple example how chain differentiation like these are done. I am not too good at differentiation

$\endgroup$
  • $\begingroup$ It is not said that "$dy/dx$ always gonna be equal to $dx/dy$", is it ? $\endgroup$ – Yves Daoust Aug 30 '18 at 9:03
3
$\begingroup$

Take $y=x^2$, which is $x=\sqrt y$.

Then

$$\frac{dx}{dy}=\frac1{2\sqrt y}=\frac1{\dfrac{dy}{dx}}=\frac1{2x}$$ seems true.

Next,

$$\frac d{dy}\left(\frac{dx}{dy}\right)=-\frac1{4y\sqrt y}=\frac d{dy}\left(\frac1{\dfrac{dy}{dx}}\right)=\frac d{dy}\left(\dfrac1{2x}\right)=\frac d{dx}\left(\dfrac1{2x}\right)\frac{dx}{dy}=-\frac1{2x^2}\frac1{2x}=-\frac1{4x^3}$$

also looks right.

$\endgroup$
0
$\begingroup$

I am confused about what you have shown and what you are interested to know...

However,the expression you have given,I think these are the alternative forms of $\dfrac{d^2 x}{dy^2}$.

Basically, we need to apply chain rule when there is a composite function. Say, $$y=f(x)=(x+1)^2$$ $$Let,g(x)=x+1$$ $$\implies y=f(x)=(g(x))^2$$ $$\implies \dfrac{dy}{dx}=2g(x).\bigg(\dfrac{d}{dx}g(x)\bigg)$$ $$\implies \dfrac{dy}{dx}=2(x+1).1=2(x+1)$$

What you have shown,I think some simplification (other forms) of double differentiation.So,you will differentiate two times respectively and will use chain rule if needed.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.